Land use of drained peatlands: Greenhouse gas fluxes, plant production, and economics. (6th November 2017) - Kasimir, Åsa; He, Hongxing; Coria, Jessica; Nordén, Anna
Abstract: Drained peatlands are hotspots for greenhouse gas (GHG) emissions, which could be mitigated by rewetting and land use change. We performed an ecological/economic analysis of rewetting drained fertile peatlands in a hemiboreal climate using different land use strategies over 80 years. Vegetation, soil processes, and total GHG emissions were modeled using the CoupModel for four scenarios: (1) business as usual—Norway spruce with average soil water table of −40 cm; (2) willow with groundwater at −20 cm; (3) reed canary grass with groundwater at −10 cm; and (4) a fully rewetted peatland. The predictions were based on previous model calibrations with several high‐resolution datasets consisting of water, heat, carbon, and nitrogen cycling. Spruce growth was calibrated by tree‐ring data that extended the time period covered. The GHG balance of four scenarios, including vegetation and soil, were 4.7, 7.1, 9.1, and 6.2 Mg CO2 eq ha −1 year −1, respectively. The total soil emissions (including litter and peat respiration CO2 + N2 O + CH4 ) were 33.1, 19.3, 15.3, and 11.0 Mg CO2 eq ha −1 year −1, respectively, of which the peat loss contributed 35%, 24%, and 7% of the soil emissions for the three drained scenarios, respectively. No peat was lost for the wet peatland. It was also found that draining increases vegetation growth, but not as drastically as peat respiration does. The cost–benefit analysis (CBA) is sensitive to time frame, discount rate, and carbon price. Our results indicate that the net benefit was greater with a somewhat higher soil water table and when the peatland was vegetated with willow and reed canary grass (Scenarios 2 and 3). We conclude that saving peat and avoiding methane release using fairly wet conditions can significantly reduce GHG emissions, and that this strategy should be considered for land use planning and policy‐making. Abstract : We performed an ecological/economic analysis of rewetting drained fertile peatlands in a hemiboreal climate over 80 years using the CoupModel and cost–benefit analysis. The GHG balance, uptake and losses through vegetation and soil, showed peat decomposition more sensitive to the soil water table depth (WTD) than the vegetation growth, with a CO2 balance at approximately 0.2 m depth, however, if including all GHG gases (also N2 O and CH4 ), the balance was more close to the soil surface, approximately 0.1 m depth. The economic analysis showed these wetter conditions to be the best.